Foraging on variable resources: the behaviour and decision making of rufous hummingbirds - Bacon, Ida Elizabeth (The University of Edinburgh, 2010)
Supplementary food is less variable than natural food. While feeding from constant food sources tends to be preferred by animals they must sometimes forage from more variable resources. However, the ways in which animals deal with the temporal and spatial variability of more natural food is not entirely understood. I investigated the decisions free-living rufous hummingbirds made when foraging from variable resources, where variability was encountered over time or within a bout via four field experiments. In addition, I investigated their use of wild flowers and differences in the use of supplementary food by these birds in different regions using surveys and by manipulating the distribution of feeders at feeding sites. I investigated the possibility of a genetic explanation for any differences in feeder use between regions using analysis of microsatellite DNA and banding data. Hummingbirds seemed to prefer to make foraging decisions based on past behaviour or post-ingestive feedback rather than on sensory information such as taste, which may be harder to assess accurately. Birds choosing between constant and variable rewards with equal means preferred the constant rewards when variability was high but tended to prefer the variable reward when variability was low. This seems to be a result of hidden time and other costs associated with foraging on highly variable resource but not on less variable ones, combined with potential benefits of information seeking from less variable resources. In addition, these preferences between constant and variable resources were affected by preceding foraging conditions. The number of birds using feeders was affected by population density and air temperature. Microsatellite data showed the rufous hummingbird population to have a fairly panmictic population structure. Investigating influences on foraging decisions at a large scale (population density) and small scale (resource variability) has provided a much wider understanding of their foraging behaviour than either could alone.
Keywords: hummingbirds; supplementary food; foraging decisions; genetic explanation